Intramural conduction system gradients and electrogram regularity during ventricular fibrillation - Jason Tri; Roshini Asirvatham; Christopher V. DeSimone; Ammar M. Killu; Alan M. Sugrue; Scott H. Suddendorf; Dorothy J. Ladewig; Suraj Kapa; Paul A. Friedman; Christopher J. McLeod; Samuel J. Asirvatham (Indian Pacing and Electrophysiology Journal, 2018)
Introduction: The His-Purkinje system has been shown to harbor triggers for ventricular fibrillation (VF) initiation. However, the substrate responsible for VF maintenance remains elusive. We hypothesized that standard, electrode-based, point-to-point mapping would yield meaningful insight into site-specific patterns and organization which may shed light on the critical substrate for maintenance of VF. Methods: VF was induced under general anesthesia by direct current (DC) application to the right ventricle in 7 acute canines. A standard EPT Blazer mapping catheter (Boston Scientific, Natuck, MA) was used for mapping in conjunction with a Prucka recording system. We collected 30 consecutive electrograms at 24 distinct sites, confirmed by fluoroscopy and intracardiac echo. These sites included both endocardial and epicardial locations throughout the ventricles and conduction system. Results: A total of 5040 individual data points were collected in 7 separate canine studies. During VF mapping, a transmural disparity was found between the epicardium (average cycle length [CL] of 1136 m s) and the endocardium (average CL of 123 m s) with a p value of <0.01. An additional, intramural gradient was found when comparing the proximal, insulated conduction system to the distal, non-insulated conduction system (average CL 218 versus 111 m s [p = 0.03]). Conclusion: Our data are supportive of a novel observation of intramural difference between insulated and non-insulated regions of the His-Purkinje network in canines. In addition, certain areas exhibited periods of regular electrogram characteristics; this was despite the heart remaining in terminal VF. These early canine data merit further study to investigate if specific ablation of the distal conduction system can perturb or extinguish VF. Keywords: Ventricular fibrillation, Purkinje, His-purkinje network, Transmural gradient, Epicardium, Endocardium, Conduction system